2023
DOI: 10.1021/acs.nanolett.2c04519
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Strain-Effect Transistor with Colossal ON/OFF Current Ratio Enabled by Reversible Nanocrack Formation in Metal Electrodes on Piezoelectric Substrates

Abstract: Extraordinarily high carrier mobility in graphene has led to many remarkable discoveries in physics and at the same time invoked great interest in graphene-based electronic devices and sensors. However, the poor ON/OFF current ratio observed in graphene field-effect transistors has stymied its use in many applications. Here, we introduce a graphene strain-effect transistor (GSET) with a colossal ON/OFF current ratio in excess of 10 7 by exploiting strain-induced reversible nanocrack formation in the source/dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…GFETs were fabricated on the PZT substrate using commercially purchased monolayer graphene films as described in our earlier work . More than 1000 GFETs were fabricated, allowing the construction of multiple SPUFs as we will elucidate later.…”
Section: Fabrication and Characterization Of Gfets On A Piezoelectric...mentioning
confidence: 99%
“…GFETs were fabricated on the PZT substrate using commercially purchased monolayer graphene films as described in our earlier work . More than 1000 GFETs were fabricated, allowing the construction of multiple SPUFs as we will elucidate later.…”
Section: Fabrication and Characterization Of Gfets On A Piezoelectric...mentioning
confidence: 99%
“…Female butterflies possess specialized chemoreceptor neurons that can detect the chemical composition of male species, which greatly influences their reproductive success. To emulate the chemisensing capability of Heliconius butterflies, we have deployed an artificial chemo-receptor neuron comprising of two graphene chemitransistors (GC1 − GC2) connected in series as shown using both optical image and circuit schematic in Figure 4a,b, respectively. (Graphene chemitransistors were fabricated on the p ++ -Si substrate using commercially purchased monolayer graphene films as described in our earlier works [60][61][62][63][64] ). Aqueous solutions of chemicals are dropped onto the graphene channel regions for chemo-sensing.…”
Section: Graphene-based Chemoreceptor Neuronsmentioning
confidence: 99%
“…However, atomic metals switches have a low reproducibility due to electrochemical reactions, which often interrupt randomly the flow of metallic ion filaments. Very recently, reversible cracks were observed in metallic source/drain electrodes of a graphene-channel ferro-FET showing an SS of 1 mV/dec at a high (40 V) gate voltage, and the switching behavior of the transistor under strain proved to be rather instable [7]. A comprehensive review of SS in FETs with atomically thin channels can be found in [8].…”
Section: Introductionmentioning
confidence: 99%